Optimum Performance Enhancing Strategies of the Gas Turbine Based on The Effective Temperatures - Thamir K., Ibrahim; M. M., Rahman; Obed M., Ali; F., Basrawi; R., Mamat (EDP Sciences, 2015, 2016)
Gas turbines (GT) have come to play a significant role in distributed energy systems due to its multi-fuel capability, compact size and low environmental impact and reduced cost. Nevertheless, the low electrical efficiency, typically about 30% (LHV), is an important obstruction to the development of the GT plants. New strategies are designed for the GT plant, to increase the overall performance based on the operational modeling and optimization of GT power plants. The enhancing strategies effect on the GT power plant’s performance (with intercooler, two-shaft, reheat and regenerative) based on the real power plant of GT. An analysis based on thermodynamics has been carried out on the modifications of the cycle configurations’ enhancements. Then, the results showed the effect of the ambient and turbine inlet temperatures on the performance of the GT plants to select an optimum strategy for the GT. The performance model code to compare the strategies of the GT plants were developed utilizing the MATLAB software. The results show that, the best thermal efficiency occurs in the intercooler-regenerative-reheated GT strategy (IRHGT); it decreased from 51.5 to 48%, when the ambient temperature increased (from 273 to 327K). Furthermore, the thermal efficiency of the GT for the strategies without the regenerative increased (about 3.3%), while thermal efficiency for the strategies with regenerative increased (about 22%) with increased of the turbine inlet temperature. The lower thermal efficiency occurs in the IHGT strategy, while the higher thermal efficiency occurs in the IRHGT strategy. However, the power output variation is more significant at a higher value of the turbine inlet temperature. The simulation model gives a consistent result compared with Baiji GT plant. The extensive modeling performed in this study reveals that; the ambient temperature and turbine inlet temperature are strongly influenced on the performance of GT plant.